Interest rate models, asset allocation and quantitative techniques for central banks and sovereign wealth funds - Berkelaar, Arjan B.; Coche, Joachim, 1967-; Nyholm, Ken. (Basingstoke, UK ; New York : Palgrave Macmillan, 2010)
"This edited volume contains essential readings for financial analysts and market practitioners working at Central Banks and Sovereign Wealth Funds. It presents the reader with state-of-the-art methods that are directly implementable, and industry 'best-practices' as followed by leading institutions in their field"--Provided by publisher.
Includes bibliographical references and index.
oif 22/06/15
Loan
Keywords: Asset-liability management; Interest rates; Asset allocation; Banks and banking, Central -- Management; Financial institutions -- Investments